Tempo and mode of mandibular shape and size evolution reveal mixed support for incumbency effects in two clades of island‐endemic rodents (Muridae: Murinae)*. (23rd April 2019) - Rowsey, Dakota M.; Heaney, Lawrence R.; Jansa, Sharon A.
Abstract: Existing radiations in a spatially limited system such as an oceanic island may limit the ecological opportunity experienced by later colonists, resulting in lower macroevolutionary rates for secondary radiations. Additionally, potential colonists may be competitively excluded by these incumbent (resident) species, unless they are biologically distinct (biotic filtering). The extant phenotypic diversity of secondary colonists may thus be impacted by lower rates of phenotypic evolution, exclusion from certain phenotypes, and transitions to new morphotypes to escape competition from incumbent lineages. We used geometric morphometric methods to test whether the rates and patterns of mandibular evolution of the Luzon "old endemic" rodent clades, Phloeomyini and Chrotomyini, are consistent with these predictions. Each clade occupied nearly completely separate shape space and partially separate size space. We detected limited support for decelerating and clade‐specific evolutionary rates for both shape and size, with strong evidence for a shift in evolutionary mode within Chrotomyini. Our results suggest that decelerating phenotypic evolutionary rates are not a necessary result of incumbency interactions; rather, incumbency effects may be more likely to determine which clades can become established in the system. Nonincumbent clades that pass a biotic filter can potentially exhibit relatively unfettered evolution.